2004
DOI: 10.1051/0004-6361:20035866
|View full text |Cite
|
Sign up to set email alerts
|

Proper motion analysis of the jet of R Aquarii

Abstract: Abstract.We have observed the jet of R Aquarii at high resolution with the VLA in 1992. 83 and in 1999.78. Observations in the first epoch have resolved the base of the jet which shows a helical structure. We cannot detect the expected new jet component at either epoch. This does not disprove the idea of periodic ejection. Either the timing inferred from the acceleration models, or the assumed periastron passage is incorrect. Alternatively, a single new component cannot be resolved due to the dense core. Prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…The centroid of this source agrees with the optical position of the star to within 10 00 (roughly one-fifth the width of our synthesized beam), implying that the continuum emission is associated with R Aqr. R Aqr has long been known to be a radio continuum source, and detections of the system have been reported previously over a wide range of frequencies (1.4Y43 GHz; e.g., Gregory & Seaquist 1974;Bowers & Kundu 1979;Sopka et al 1982;Spergel et al 1983;Hollis et al 1985;Dougherty et al 1995;Hollis et al 1997;Mäkinen et al 2004). At high resolution, the continuum emission breaks up into multiple components, including a compact H ii region centered at the position of the AGB star and a jet extended $6 00 to the northeast (e.g., Kafatos et al 1983;Hollis et al 1985;Dougherty et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The centroid of this source agrees with the optical position of the star to within 10 00 (roughly one-fifth the width of our synthesized beam), implying that the continuum emission is associated with R Aqr. R Aqr has long been known to be a radio continuum source, and detections of the system have been reported previously over a wide range of frequencies (1.4Y43 GHz; e.g., Gregory & Seaquist 1974;Bowers & Kundu 1979;Sopka et al 1982;Spergel et al 1983;Hollis et al 1985;Dougherty et al 1995;Hollis et al 1997;Mäkinen et al 2004). At high resolution, the continuum emission breaks up into multiple components, including a compact H ii region centered at the position of the AGB star and a jet extended $6 00 to the northeast (e.g., Kafatos et al 1983;Hollis et al 1985;Dougherty et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…There is also the elongated two-sided jet structure in NE and SW directions and associated arcs extending to about 30 arcsec from the central source. The bright "jet spike" initially detected around 1980 has moved radially out with an angular speed of about 0.2 /yr (e.g., Mäkinen et al 2004) and it is now the prominent elongated feature at about 10 arcsec to the NE of the central source.…”
Section: Introductionmentioning
confidence: 99%
“…The jet outflow pattern in R Aqr is quite complex with measured proper motions corresponding to tangential speeds between 50 and 250 km s −1 and radial velocities from −100 km s −1 to +100 km s −1 (Solf & Ulrich 1985;Hollis et al 1997a;Navarro et al 2003;Mäkinen et al 2004). The overall flow pattern of the NE jet spike corresponds to an outflow away from the central binary, with a velocity of about 150 km s −1 and a radial velocity component of −70 km s −1 (towards us).…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of the orbit during the eclipse is uncertain, however. From the duration of the eclipse, Mäkinen et al (2004) claimed that it occurs at apastron, while McIntosh & Rustan (2007) suggested that it happens during periastron passage. The latter authors also obtained an orbital period of 34.6 yr, significantly shorter than the other estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the jets were intensively studied (e.g. Hollis et al 1990Hollis et al , 1991Viotti et al 1987;Mäkinen et al 2004;Nichols et al 2007). Kellogg et al (2007) observed both jets in X-ray and radio emission and found the NE jet to be curved and dominated by a bright spot 8 from the star.…”
Section: Introductionmentioning
confidence: 99%